Deteksi Dini Kanker Payudara Menggunakan Metode Gans (Generative Adversarial Network) Dilihat Dari Segi Filosofi: Narrative Review (NR) - Samsinar, Samsinar; Afriany, Renny (NHM PRESS, 2024)
Early detection of cancer using artificial intelligence (AI) from a healthcare perspective is crucial as it significantly increases the chances of successful treatment and reduces the risk of mortality. This aspect is emphasized as a vital factor in enhancing early cancer detection in patients and improving survival rates from a philosophical perspective. This article highlights that early detection can also help reduce the high costs associated with cancer treatment. By identifying the disease at an early stage, patients may require less intensive and less expensive treatment, which can alleviate the burden on both patients and their families. However, there are challenges, as over time, breast cancer becomes more difficult to treat, leading to a decrease in survival rates, necessitating the implementation of effective early detection methods. The development of pattern recognition methods is discussed as a means to improve the accuracy of early cancer detection. The results present a framework for analyzing human-computer interaction that incorporates a philosophical perspective, providing a structured approach to evaluating the implications of technology on human life.